Holey graphenes as the conductive additives for LiFePO4 batteries with an excellent rate performance. (August 2019) - Xu, Lingtao; Lv, Wei; Shi, Kai; Xiao, Shujie; You, Conghui; He, Yan-Bing; Kang, Feiyu; Yang, Quan-Hong
Abstract: Graphene has been investigated and widely used as the high performance conductive additives in lithium ion batteries. Unfortunately, the LiFePO4 batteries with graphene additives present quite a low rate performance because the graphene with planar structure blocks the Li ion transportation. Herein, a binary conductive additive containing only 1 wt% holey graphene (HG) and 1 wt% Carbon Black such as Super-P (SP) has been developed, which achieves excellent high-rate performance for the LiFePO4 battery that is comparable to that of the battery with 10 wt% SP. The HG with large amount of holes and large specific surface area substantially enhances the electronic conductivity of LiFePO4 electrode, but not compromises the high efficient ionic transportation. A small content of SP as the supplement of long-range conductive network formed by HG can contact the LiFePO4 sufficiently for achieving excellent conductivity in the whole LiFePO4 electrode. A balance of electronic conductivity and ionic diffusivity can be achieved using the HG and SP simultaneously. The HG and SP with low content can synergistically construct an excellent ionic and electronic conductive network in LiFePO4 electrode. This study may promote the commercial applications of HG additives for high performance LiFePO4 batteries. Graphical abstract: Image 1